(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The term video compression refers to the process of encoding a video file in a way thatresults in a smaller file size. It can be difficult to record a lengthy video sequence due to the size of theresulting video files. When a video is compressed, its file size is decreased because unnecessaryinformation is removed. Compressing a video involves a lengthy procedure in which the original files arereduced in size significantly. Video coding is what establishes the efficiency of compression on liveactionentertainment videos collaborative mobile communication situation needed to access the littlevideo frames of predetermined dimensions. The quantity of data needed to depict a video frame isdrastically decreased without a noticeable drop in image quality. Most commonly used video encodingprotocols, including H.264 and H.263, compress video frames before sending them over the network.This study explicitly gives an insight into the theoretical aspects and background of video encoding andvideo compression.